Management of periradicular pathosis by single visit endodontic treatment using calcium hydroxide and mineral trioxide aggregate based sealer - Sheikh, Md Abdul Hannan; Khalifa, Eyad Al; Hossain, Mozammal; Hossain, Md Faruk; Karim, Nazneen; Quader, SM Abdul; Karim, Fahd AA; Shaikh, Abdul Kader (Update Dental College Journal, 2020)
In this study, 120 teeth having periradicular pathosis were treated with single visit root canal treatment and then obturated with either calcium hydroxide containing sealer or mineral trioxide aggregate based sealer. The healing of periradicular pathosis was examined at 3, 6, and 12 months by clinical and radiological evaluation. Collected data were analyzed with standard statistical methods by using SPSS version- 20. The results showed that at 3 and 6 months, the differences between calcium hydroxide containing sealer or mineral trioxide aggregate based sealer were not statistically significant. However, the healing capability of periapical radiolucency at 12 months between two groups was statistically significant (P=0.03). The final outcome of the clinical and radiological investigation showed successful results of 96.6% and 98.1% in calcium hydroxide and mineral trioxide aggregate group, respectively. In conclusion, both calcium hydroxide and mineral trioxide aggregate based sealers are almost equally effective in single visit root canal therapy for the management of periradicular pathosis. Update Dent. Coll. j: 2020; 10 (2): 10-13